Analisis Potensi Pengembangan Agribisnis Kedelai di Wilayah Lahan Kering Kabupaten Lombok Tengah Nusa Tenggara Barat - Ayu, Candra; Wuryantoro, Wuryantoro; Nursan, Muhammad (JIA (Jurnal Ilmiah Agribisnis) : Jurnal Agribisnis dan Ilmu Sosial Ekonomi Pertanian, 2021)
Soybean is a strategic food in Indonesia whose needs continue to increase. However, efforts to increase local soybean production are still difficult due to the large number of imported soybeans entering. This fact has resulted in a decline in farmers' interest in soybean cultivation. In addition, programs to increase local soybean production are still focused on irrigated land, whose use is still competitive with corn and rice. Therefore, this study aims to 1) assess the production and socio-economic potential of soybean agribusiness, 2) determine the added value of soybean-based agroindustries, and 3) estimate the need for soybeans on an agro-industrial scale that makes farmers in the dry land of Central Lombok prosperous. This research was conducted for four months, starting from June to October 2020. The number of research respondents was 30 respondents who were selected by purposive sampling. The results showed that soybean productivity was 5.75 Ku / hectare and income was IDR 2,433,588.88 / hectare. The added value of the farming family for the tofu agroindustry is Rp. 7,989, and the Tempe agroindustry is Rp. 5,131. The minimum amount of soybean needed for the tofu and tempeh agroindustry or the farmer's family to be prosperous is 1,365.38 kg/capita/year. This improvement is expected to be an incentive to foster farmer interest so that soybean production can increase.